Increasing Soil Suppressivity to Fusarium Wilt Of Banana Through Banana Intercropping with Allium spp. - Arif Wibowo; Aulia Rahman Alboneh; Medina Uli Alba Somala; Siti Subandiyah; Tony Pattison; Agustin Molina (Jurnal Perlindungan Tanaman Indonesia, 2015)
Fusarium wilt, caused by Fusarium oxysporum f.sp. cubense (Foc), is one of the most destructive diseases of banana and has spread in many plantation areas in Indonesia. Until today, the effective ways to control banana fusarium wilt disease have not yet been found. Some studies indicated thatAllium spp. could be used to suppress plant diseases caused by Fusarium. Allium spp. are important horticultural crops which are generally cultivated in some areas in Indonesia. This research was conducted to determine the effect of several species ofAllium spp. intercropped with banana to improve soil suppressiveness against banana fusarium wilt disease. The results showed that up to 12 months after planting, from 3 species ofAllium spp. (A. tuberosum/ Chinese leek, A. fistulosum/ bunching onion, and A. cepa var. aggregatum/ shallot) intercropped with banana Ambon Kuning (AAA) cultivar, Chinese leek and shallot were able to suppress the incidence of fusarium wilt disease of banana by 46 and 33% respectively. Soil analysis on the rhizosphere of banana intercropped with Chinese leek and shallot had lower population of total Fusarium compared to the other treatments. Analysis of fluorescein diacetate (3’.6’-diacetylfluoerescein) or FDA also showed that total microbial activity in the rhizosphere of banana intercropped withAllium spp. was also lower compared to control treatment (without intercropping). The observation of the effect ofAllium spp. extracts on Foc showed that Allium spp. extracts were able to suppress the development of the colony and spore germination of Foc in vitro. INTISARILayu Fusarium, yang disebabkan oleh Fusarium oxysporum f.sp. cubense (Foc), merupakan salah satu penyakit tanaman pisang yang paling merusak dan telah tersebar di berbagai daerah di Indonesia. Sampai saat ini cara yang efektif untuk mengendalikan penyakit layu fusarium pisang belum ditemukan. Beberapa penelitian menunjukkan bahwa Allium spp. dapat dipergunakan untuk menekan penyakit tumbuhan yang disebabkan oleh Fusarium. Allium spp. adalah tanaman hortikultura penting yang banyak dibudidayakan di Indonesia. Penelitian ini dilakukan untuk mengetahui pengaruh beberapa spesiesAllium spp. yang ditumpangsarikan dengan tanaman pisang untuk meningkatkan supresifitas tanah dalam menekan penyakit layu fusarium pisang. Hasil pengamatan menunjukkan bahwa sampai 12 bulan setelah tanam, dari 3 spesiesAllium spp. (A. tuberosum/kucai, A. fistulosum/loncang, dan A. cepa var. aggregatum/bawang merah) yang ditumpangsarikan dengan pisang kultivar Ambon Kuning (AAA), kucai dan bawang merah mampu menekan insidensi penyakit layu fusarium pisang berturut-turut sebesar 46% dan 33%. Analisis tanah rhizosfer pisang yang ditumpang sari dengan kucai dan bawang merah menunjukkan populasi total Fusarium yang lebih rendah daripada perlakuan lainnya. Analisis fluorescein diacetate (3’.6’-diacetylfluoerescein) atau FDA juga menunjukkan bahwa aktivitas total mikrobia pada rhizosfer pisang yang ditumpang sari dengan Allium spp. lebih rendah jika dibandingkan dengan perlakuan kontrol (tanpa tumpang sari). Pengamatan pengaruh ekstrak Allium spp. terhadap Foc menunjukkan bahwa ekstrak Allium spp. mampu menekan perkembangan koloni dan perkecambahan spora Foc secara in vitro.